PEMANFAATAN “BOOK CREATOR” DALAM PEMBELAJARAN LITERASI DIGITAL UNTUK MENINGKATKAN MINAT DAN HASIL BELAJAR MATA PELAJARAN “PRODUK KREATIF DAN KEWIRAUSAHAAN” - Farkhanah, Eriana (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
The purpose of this study is expected to be more interesting and fun learning of creative and entrepreneurial products by utilizing meaningful digital literacy technology; the percentage of student participation and activity increases ; the results of learning creative and entrepreneurial products have increased with the use in meaningful digital literacy learning; and the use of certain digital information technology applications can increase the willingness and desire to read and study the subject matter. This research is a type of Class Action Research (PTK) which consists of 2 cycles. This research was carried out at SMK Negeri 1 Wonosari, with the subjects of the study being 36 students of class XI OTKP 2. The object under study is the student's interest in learning and the learning outcomes of Creative and Entrepreneurial Products. Data collection was carried out using pre-tests, assessment results in Cycles I and II, questionnaires, and observations. Data analysis is carried out by comparing the initial data with the final data after the action. The results showed that the use of "Book Creator" in meaningful literacy learning can increase student interest and learning outcomes. The increase in interest and learning outcomes of students can be seen from the average learning outcomes that have increased completeness from 75 in the initial data with a graduation percentage of 72.22% to 85 with a completion percentage of 75% in cycle I. In cycle II the average learning outcomes increased to 87 with a percentage of completion reaching 94.44%.